Labor Absorption in Bulukumba Regency: an Analysis of the Agricultural Sector and the Industrial Sector - Isnada Arsam (Bulletin of Economic Studies (BEST), 2021)
The increasing production of the agricultural sector in Bulukumba Regency makes the agricultural sector a dominant contribution in the formation of the economic structure, and has a significant influence on the absorption of labor. Agriculture as a labor-intensive sector in absorbing labor does not require high educational qualifications so that the population's dependence on this sector remains high. In addition to the orientation of increasing agricultural production for food security, it also provides broad access to employment opportunities. Meanwhile, the industrial sector as the leading sector is expected to continue to grow and strengthen the agricultural sector. The industrial sector in Bulukumba Regency has a significant influence on employment. Industrial growth and diversification is very important to be developed to maximize its potential and can absorb a more massive workforce in the next period. Keywords: Agriculture, Industry, Labor Absorption.